(untitled) (CIPEEX, 2025)
Introduction: Leprosy, caused by Mycobacterium leprae, is an infectious and granulomatous disease that predominantly affects peripheral nerves, mucous membranes, and skin. However, it can affect and trigger vascular manifestations that, in this sense, can coexist with or even simulate primary vasculitis. The histopathology of leprosy can mimic that of other infectious entities when the clinical information provided is vague, since several inflammatory cells coexist in the infectious process, and the interface between leprosy and vasculitis represents a challenge of great clinical relevance due to diagnostic overlap. Objective: The objective of this study is to analyze the implications of diagnostic similarity between these vascular and infectious pathologies. Method: This is a literature review in a simple summary format, using the National Library of Medicine (PubMed) and Virtual Health Library (VHL) as the database, using the following Science and Health Descriptors (DeCS): "Leprosy," "Vasculitis," and "Infection." Five articles published in English between 2021 and 2024 were selected. Results: It was found that leprosy can mimic vasculitis or induce vasculitic phenomena, making diagnostic differentiation essential, since substantially different therapeutic approaches, if applied incorrectly, can result in more serious clinical outcomes, such as exacerbation of the infection or irreversible damage to target organs. Furthermore, perivascular granulomatous inflammation can induce an intense vascular immune response and result in indirect damage, with signs of ischemia and tissue necrosis, manifestations also observed in primary vasculitis. In addition, a misdiagnosis when treating leprosy vasculitis as a primary autoimmune condition with isolated suppression can aggravate the infectious disease, increase the bacterial load, and accelerate the onset of permanent disabilities. Furthermore, confusing primary vasculitis with leprosy delays the institution of adequate immunosuppression, which favors the progression of lesions and permanent damage. Furthermore, confusing primary vasculitis with leprosy delays the institution of adequate immunosuppression, which favors the progression of lesions and permanent damage. This condition reinforces the importance of an accurate diagnosis that differentiates leprosy and vasculitis, in order to ensure the therapeutic efficacy of these pathologies. Conclusion: Given the above, it was evidenced that the relationship between the similarities in the clinical and histopathological manifestations of leprosy and vasculitic phenomena corroborates inaccurate or delayed diagnoses, especially in endemic regions. This reinforces the need for accurate differential diagnosis within clinical and laboratory evaluations, which includes clinical, epidemiological, laboratory, histopathological, and molecular data, aiming to reduce the risks of inappropriate pharmacological therapies, in addition to reducing morbidity and mortality and improving patients’ quality of life.